Who does what and why? Intra-household roles and explanatory models for sourcing soybean seed from the formal sector in Malawi - Cole, Steven M.; Feleke, S.; Manda, J.; Gondwe, T.; Akinwale, M.G. (SAGE Publications, 2021)
This study asks whether there is utility in knowing who sources soybean seed within the household and why when explaining variation in seed obtained from the formal versus informal sector. Survey data collected in Malawi in 2018 were used to explore the question. Results suggest that the identity of the person who sources seed has little to do with whether the seed was obtained from the formal sector. Instead, why the person sources soybean seed is the better predictor. As formal seed system actors mobilize to persuade more smallholder farmers to adopt improved varieties, understanding why people source seed may be key for targeting and when designing agricultural development interventions.